Production of jet fuel range paraffins by low temperature polymerization of gaseous light olefins using ionic liquid. (15th July 2016) - Jiang, Peiwen; Wu, Xiaoping; Zhu, Lijuan; Jin, Feng; Liu, Junxu; Xia, Tongyan; Wang, Tiejun; Li, Quanxin
Graphical abstract: A novel catalytic transformation of light olefins into jet fuel range iso-paraffins by the low-temperature olefin polymerizations under atmospheric conditions. Highlights: A novel transformation of light olefins to jet fuel range paraffins was demonstrated. The synthetic fuels can be produced by atmospheric olefin polymerizations. C8 –C15 iso-paraffins from light olefins was achieved with a selectivity of 80.6%. Abstract: This work demonstrated a novel catalytic transformation of gaseous olefins into jet fuel range iso-paraffins by the low-temperature olefin polymerizations under atmospheric conditions. The production of the desired C8 –C15 iso-paraffins with the selectivity of 80.6 C mol% was achieved by the room-temperature polymerizations of gaseous light olefins using the [BMIM] Al2 Cl7 ionic liquid. The influences of the reaction conditions on the olefinic polymerizations were investigated in detail. The properties of hydrocarbons in the synthetic fuels were determined by the GC–MS analyses combined with 1 H NMR, and 13 C NMR analyses. The formation of C8 –C15 hydrocarbons from gaseous light olefins was illustrated by the identified products and the functional groups. This transformation potentially provides a useful avenue for the production of the most important components of iso-paraffins required in jet fuels.